Global well-posedness for the compressible non-resistive MHD equations in a 3D infinite slab. (February 2023) - Zhao, Youyi
Abstract: In this paper, we investigate the existence and uniqueness of global strong solutions to the system of compressible viscous non-resistive MHD equations in a three-dimensional horizontally infinite slab with finite height. We first reformulate our analysis to Lagrangian coordinates, and then develop a new mathematical approach to establish global well-posedness of the MHD system, which requires no compatibility conditions on the initial data.